The confounding effects of logging on tree seedling growth and herbivory in Central Amazon - Darrigo, Maria Rosa; dos Santos, Flavio A. M.; Venticinque, Eduardo M. (Biotropica, 2018)
Light availability is an important modulator of seedling growth and plant–herbivore dynamics. Logging increases light levels in forests, potentially altering herbivore–plant interactions that drive seedling establishment. We conducted a transplant experiment to evaluate how logging and herbivory affect seedling growth and survival in three shade-tolerant tree species, at paired canopy gap and understory sites in logged forest and an adjacent unlogged area in central Amazonia (Brazil). Seedlings were either left exposed to naturally occurring insect herbivores or protected from insects by a fine netting structure. We measured the herbivore damage and growth rate of seedlings after 18 mo. In general, logged areas received more light than unlogged sites. Growth and herbivory rates were positively influenced by light, and herbivory was also influenced positively by logging. In gaps, increased growth mitigated foliar damage. Logging resulted in a loss of foliar tissue due to increased herbivory. Herbivory rates were higher in the understory of logged sites than in that of unlogged understory sites, but growth was similar in these areas. Thus, the understory of logged areas provided the least favorable sites for shade-tolerant tree regeneration, due to higher herbivory rates. The effect of logging on biotic interactions can extend beyond the gaps it creates into untouched understory sites. To our knowledge, this is the first time such a pattern has been observed, highlighting the importance of evaluating the impact of logging on biotic interactions.